Developing Dynamics of Teacher’s Professional Identity - Dilmurod Abdusamiyev (Penerbit Jurnal Indonesia, 2024)
the article describes the main directions of the teacher’s professional activity, their influence on the development of professional identity, the stages of the formation of the self-concept and the scientific-methodical analysis of the development criteria, as well as suggestions and recommendations for the effective organization of professional activity.